Answer:
Explanation:
Before we differentiate, let us assign a variable to the function. Let y be equal to the function i.e let y = 3√x -2/x²
In differentiation if
, then
where n is a constant and dy/dx means we are differentiating the function y with respect to x.
Applying the formula o the question given;
![y= 3√(x) -2/x^2\\y = 3{x}^(1)/(2) - 2x^(-2) \\\\](https://img.qammunity.org/2021/formulas/mathematics/college/itqus60z92d47zbjnhwlw5mz306dxsvajj.png)
On differentiating the resulting function;
![(dy)/(dx) = (1)/(2)*3x^{(1)/(2)-1 } - (-2)x^(-2-1) \\\\(dy)/(dx) = (1)/(2)*3x^{-(1)/(2)} + 2x^(-3)\\ \\(dy)/(dx) = (1)/(2)*{\frac{3}{x^{(1)/(2) } }} + (2)/(x^(3) ) \\\\(dy)/(dx) = {\frac{3}{2x^{(1)/(2) } }} + (2)/(x^(3) )\\\\(dy)/(dx) = {(3)/(2√(x) )} + (2)/(x^(3) )](https://img.qammunity.org/2021/formulas/mathematics/college/peio2qwajgtggpq9ovvp7vg919925kbt6k.png)
To combine the terms, we will add up by finding their LCM.
![(dy)/(dx) = {(3)/(2√(x) )} + (2)/(x^(3) )\\(dy)/(dx) = (3x^3+4√(x) )/(2x^(3) √(x))](https://img.qammunity.org/2021/formulas/mathematics/college/zrjuq46osmd8j6o5nysa5cvza6og2gik5f.png)